A função do tutor na Educação a distância: desafios e perspectivas na Universidade Estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The present research has as investigation universe the Pedagogy course offered in the distance modality by the State University of Goiás (UEG) in partnership with the Open University of Brazil (UAB). When we consider the frequent technological transformations widely used in Distance Education, we are faced with the following question for carrying out the research: In addition to its didactic-pedagogical activities already consolidated and practiced in the teaching and learning process that other means, resources, instruments and/or or tools do tutors (teacher-tutors) build and use (or not) to face the challenges and difficulties experienced in their daily professional practices? We clarify that the teaching practice, both of the teacher and the tutor, is constituted by different pedagogical functions, by different didactic materials, under the responsibility of both about the disciplines that make up the curricular matrices, fundamental for the mediation and development of the teaching and learning process. With a view to carrying out this research, we defined the general objective of analyzing how the tutor uses his pedagogical functions to create new learning perspectives and overcome his challenges in the teaching-learning process of students in the Pedagogy course at the University of São Paulo. Beautiful Waters of Goiás. In order to achieve our intentions between meetings and disagreements, we proposed to analyze the information made available by the subjects who answered the questions of our investigation in their realities and in the concreteness of their experiences in the exercise of the function of tutor of the teaching and learning process in the distance modality . Our expectation with the conclusion of this study is that it can contribute to the understanding of the historical contexts that involve our country regarding the opportunities for academic training at a higher level for a portion of the Brazilian population, without failing to consider its weaknesses and deficiencies, as despite being a possibility, in fact, it constitutes a concession by the ruling class as a palliative.
The tutor's role in Distance Education: challenges and perspectives at the State University of Goiás
Keywords: EaD na UEG; Pedagogia na Modalidade à Distância; Funções Pedagógicas - Tutor em EaD; Distance Education at UEG; Pedagogy in Distance Mode; Pedagogical Roles - Tutor in Distance Learning.; CIENCIAS HUMANAS::EDUCACAO